AC-DC power system analysis - Arillaga, J.; Smith, Bruce (London, United Kingdom Institution of Electrical Engineers, 1998)
The following topics are dealt with: AC-DC converter; power flow solution; harmonic solution; three-phase power and harmonic flow; electromagnetic transient simulation; electromechanical stability and transient converter simulation.
Electronic reproduction.
Keywords: Electric power systems -- Mathematical models; Electronic books